Targeted methylation testing of a patient cohort broadens the epigenetic and clinical description of imprinting disorders. Issue 9 (2nd August 2013) - Poole, Rebecca L.; Docherty, Louise E.; Al Sayegh, Abeer; Caliebe, Almuth; Turner, Claire; Baple, Emma; Wakeling, Emma; Harrison, Lucy; Lehmann, Anna; Temple, I. Karen; Mackay, Deborah J.G.; ,
Abstract: Imprinting disorders are associated with mutations and epimutations affecting imprinted genes, that is those whose expression is restricted by parent of origin. Their diagnosis is challenging for two reasons: firstly, their clinical features, particularly prenatal and postnatal growth disturbance, are heterogeneous and partially overlapping; secondly, their underlying molecular defects include mutation, epimutation, copy number variation, and chromosomal errors, and can be further complicated by somatic mosaicism and multi‐locus methylation defects. It is currently unclear to what extent the observed phenotypic heterogeneity reflects the underlying molecular pathophysiology; in particular, the molecular and clinical diversity of multilocus methylation defects remains uncertain. To address these issues we performed comprehensive methylation analysis of imprinted genes in a research cohort of 285 patients with clinical features of imprinting disorders, with or without a positive molecular diagnosis. 20 of 91 patients (22%) with diagnosed epimutations had methylation defects of additional imprinted loci, and the frequency of developmental delay and congenital anomalies was higher among these patients than those with isolated epimutations, indicating that hypomethylation of multiple imprinted loci is associated with increased diversity of clinical presentation. Among 194 patients with clinical features of an imprinting disorder but no molecular diagnosis, we found 15 (8%) with methylation anomalies, including missed and unexpected molecular diagnoses. These observations broaden the phenotypic and epigenetic definitions of imprinting disorders, and show the importance of comprehensive molecular testing for patient diagnosis and management. © 2013 Wiley Periodicals, Inc.